2012
DOI: 10.4012/dmj.2012-105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermo-mechanical load cycling on silorane-based composite restorations

Abstract: The aim of this study was to compare the formation of marginal gaps after thermo-mechanical load cycling, between siloranebased and methacrylate-based restorations. Standardized class II cavities were made in 10 permanent human third molars that were restored with the adhesive system Clearfil SE Bond+composite Filtek Z-350 (Methacrylates) and with the composite bonding Filtek P90+P90 (Siloranes), respectively. After 24 h of storage in 100% humidity at 37°C, the restoration margins were stained, photographed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Repeated temperature fluctuations in the oral cavity may induce degradation of resin-hydoxyapatite bonds due to differences in thermal expansion coefficients between enamel hydroxyapatite and the infiltration resin. 38,39 Thermal stress may also affect the surface integrity of resin-infiltrated enamel lesions as indicated by the presence of surface microcracks and microfissures after thermocycling challenges (Figure 3). These changes in surface properties may contribute to staining and discoloration of resin-infiltrated surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated temperature fluctuations in the oral cavity may induce degradation of resin-hydoxyapatite bonds due to differences in thermal expansion coefficients between enamel hydroxyapatite and the infiltration resin. 38,39 Thermal stress may also affect the surface integrity of resin-infiltrated enamel lesions as indicated by the presence of surface microcracks and microfissures after thermocycling challenges (Figure 3). These changes in surface properties may contribute to staining and discoloration of resin-infiltrated surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…These stresses are expected to increase the width of existent gaps or develop other gaps. Increased gaps have been demonstrated after mechanical and/or thermal cycling 4,8,22 . Contradictorily, this was not observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Alternating temperature fluctuations in the oral environment may enhance bond degradation between the infiltrating resin and enamel hydoxyapatite because of differences in coefficients of thermal expansion between them. 28,29 Regarding surface roughness, our results indicated that resin infiltration could provide smoother enamel surface, as compared to untreated lesions. On exposure to thermal challenge, Icontreated specimens could maintain smoother surface, both at 5000 and 10,000 cycles.…”
Section: Discussionmentioning
confidence: 71%